Henrik Ibsen’s The Wild Duck: A Research-Based Study of the Psychosocial Risk Factors of Hedvig’s Suicide - Safaa Fahes (European Scientific Journal, ESJ, 2023)
Adolescent suicide, an issue raised in literature, represents a key moment in Henrik Ibsen’s play, The Wild Duck. Even though the literature available on the play refers to the suicidal act performed by Hedvig by accusing either mysterious fate or particular characters of driving the girl to her doom, the interpretations are apparently few and far between and do not provide analysis of the reasons behind the suicide in one detailed research. This paper, thus, provides a comprehensive study of these factors, using a qualitative analysis of the play that relies on study results gleaned from both sociological and psychological researches examining the risk factors that aggravate the probability of suicide in adolescents. Based on this approach, the paper reveals the role of family conflicts, neglect, personal susceptibility in adolescence, isolation, impaired schooling, economic hardship, and inclination towards self-sacrifice for the sake of the family, in causing the adolescent girl’s death by suicide in the closing scene of the play. The significance of this research lies in its contribution to a deeper understanding of suicide in literary works. The implications of the study extend beyond the realm of literature, giving more insight into the driving forces behind suicide in adolescents, in the hope that intervention methods may alleviate such factors.